Women and work: What role do social norms play? - Andreia Tolciu; Ulrich Zierahn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Against the background of the current economic research which concentrates particularly on individual and structural factors, this paper examines if and to what extent social norms (in terms of attitudes towards gender roles and work commitment) can make a complementary statement in explaining women's employment status. The impact is presumed to be enhanced through norms shared by people belonging to the same households, through norms shared by people belonging to the same households, The analysis relies on a rich German dataset and employs a zero inflated negative binomial model. The results highlight the importance of 'relevant others' in explaining women's employment status.
Keywords: A13; C35; J16; J21; 330; women's employment status; households and families; social norms; zero inflated negative binominal model; Weibliche Arbeitskräfte; Soziale Norm; Arbeitsethik; Schätzung; Deutschland